'Mode 3' and 'Quadruple Helix': toward a 21st century fractal innovation ecosystem. (23rd February 2009) - Carayannis, Elias G.; Campbell, David F.J.
'Mode 3' allows and emphasises the co-existence and co-evolution of different knowledge and innovation paradigms: the competitiveness and superiority of a knowledge system is highly determined by its adaptive capacity to combine and integrate different knowledge and innovation modes via co-evolution, co-specialisation and co-opetition knowledge stock and flow dynamics. The 'Quadruple Helix' emphasises the importance of also integrating the perspective of the media-based and culture-based public. What results is an emerging fractal knowledge and innovation ecosystem, well-configured for the knowledge economy and society.